Mechanical properties of high-performance concrete reinforced with basalt fibers - Ayub, T. (Elsevier Ltd, 2014)
Knowledge of the concrete properties such as strength, elastic modulus, thermal expansion, heat generation, shrinkage and creepand durability, are important in the pavement designing. High-performance fiber reinforced concrete (HPFRC) is currently being used in the construction of airport runway and highway pavements but mostly it is used forrapid cure patching and where the early opening of the pavement is required. The reason for less use of HPFRC is its high cost as it employs higher cement content whichresults in thermal contraction problems due to high heat release during setting. In this study, material properties of an economical HPFRC containing Basalt fibers are determined which include compressive strength, elastic modulus and tensile strength. Basaltfibers are relatively cheaper and newfibres for concrete whichare recently investigated by a few researchers. In this study, influence of addition of 1, 2 and 3 Basaltfiber volume fraction in three different mixes of high-performance concrete (HPC) is investigated. The first mix was prepared by using 100 cement and other two mixes were prepared by replacing 10 cement content with silica fume and locally produced met kaolin. Experimental results showed that the addition of Basaltfibersup to 2 fiber volume together with mineral admixtures improved the compressive strength. The improvement in the strains corresponding to maximum compressive strength and splitting tensile strength results was observed at all fiber volumes, whereas there is a negligible influence of the fiber addition on the elastic modulus. Â© 2014 The Authors. Published by Elsevier Ltd.